Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation terhadap Motivasi Belajar PAK Siswa Kelas IX di SMP Negeri 1 Simanin do, Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Angel Sri Wulan Manalu; Oktober Tua Aritonang; Risden Anakampun; Boho Pardede; Simion Harianja (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The aim of this research is to determine the positive and significant influence of implementing the Group Investigation Type Cooperative Learning Model on the Learning Motivation of PAK Class IX Students at SMP Negeri 1 Simanindo, Samosir Regency for the 2023/2024 Academic Year. The research method used is a quantitative method and a pre-experimental design research type in the form of "One Shot Case Study". The population was all class IX students of SMP Negeri 1 Simanindo, totaling 189 people and a sample of 32 people was determined using the Purposive Sample technique. Data was collected using a research instrument of 36 items, namely 16 items for variable 0.05,n=32) = 0.349. b) Testing a significant relationship obtained a value of tcount= 4.354 > ttable(a=0.05,dk=n-2=30)= 2.042. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂="16.45"+0.98X. b) Regression coefficient of determination test (r2) = 38.7%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=13, dk denominator=n-2=32-2=30) namely 18.94 > 2.09. Shows that there is a positive and significant influence of the application of the Group Investigation Type Cooperative Learning Model on the PAK Learning Motivation of Class IX Students of SMP Negeri 1 Simanindo, Samosir Regency for the 2023/2024 Academic Year. Thus Ha is accepted and H0 is rejected.